Development of a mouse model for pulp-dentin complex regeneration research: a preliminary study - Kim, Sunil (Restor Dent Endod, 2019)
OBJECTIVES: To achieve pulp-dentin complex regeneration with tissue engineering, treatment efficacies and safeties should be evaluated using in vivo orthotopic transplantation in a sufficient number of animals. Mice have been a species of choice in which to study stem cell biology in mammals. However, most pulp-dentin complex regeneration studies have used large animals because the mouse tooth is too small. The purpose of this study was to demonstrate the utility of the mouse tooth as a transplantation model for pulp-dentin complex regeneration research. MATERIALS AND METHODS: Experiments were performed using 7-week-old male Institute of Cancer Research (ICR) mice; a total of 35 mice had their pulp exposed, and 5 mice each were sacrificed at 1, 2, 4, 7, 9, 12 and 14 days after pulp exposure. After decalcification in 5% ethylenediaminetetraacetic acid, the samples were embedded and cut with a microtome and then stained with hematoxylin and eosin. Slides were observed under a high-magnification light microscope. RESULTS: Until 1 week postoperatively, the tissue below the pulp chamber orifice appeared normal. The remaining coronal portion of the pulp tissue was inflammatory and necrotic. After 1 week postoperatively, inflammation and necrosis were apparent in the root canals inferior to the orifices. The specimens obtained after experimental day 14 showed necrosis of all tissue in the root canals. CONCLUSIONS: This study could provide opportunities for researchers performing in vivo orthotopic transplantation experiments with mice.